8th International Conference on Engineering, Project, and Product Management (EPPM 2017) Proceedings (Lecture Notes in Mechanical Engineering,, 2018)
This book presents the proceedings of the 8th International Conference on Engineering, Project, and Product Management (EPPM 2017), highlighting the importance of engineering, project and product management in a region of the world that is in need of transformation and rebuilding. The aim of the conference was to bring together the greatest minds in engineering and management and offer them a platform to share their innovative, and potentially transformational, findings. The proceedings are comprehensive, multidisciplinary, and advanced in their approach with an appeal not only for academicians and university students but also for professionals in various engineering fields, especially construction, manufacturing and production.